Aspects of intradermal immunization with different adjuvants: The role of dendritic cells and Th1/Th2 response - Oreskovic, Zrinka; Nechvatalova, Katerina; Krejci, Josef; Kummer, Vladimir; Faldyna, Martin (PloS one, 2019)
Intradermal (i.d.) application of vaccine is promising way how to induce specific immune response against particular pathogens. Adjuvants, substances added into vaccination dose with the aim to increase immunogenicity, play important role in activation of dendritic cells with subsequent activation of lymphocytes. They can, however, induce unwanted local reactions. The aim of the study was to determine the effect of i.d. administration of model antigen keyhole limped hemocyanine alone or with different adjuvants-aluminium hydroxide and oil-based adjuvants-on local histopathological reaction as well as dendritic cell activation at the site of administration and local cytokine and chemokine response. This was assessed at 4 and 24 hours after application. Selection of the adjuvants was based on the fact, that they differently enhance antibody or cell-mediated immunity. The results showed activation of dendritic cells and both Th1 and Th2 response stimulated by oil-based adjuvants. It was associated with higher expression of set of genes, incl. chemokine receptor CCR7 or Th1-associated chemokine CXCL10 and cytokine IFNγ. Application of the antigen with aluminium hydroxide induced higher expression of Th2-associated IL4 or IL13. On the other hand, both complete and incomplete Freund´s adjuvants provoked strong local reaction associated with influx of neutrophils. This was accompanied with high expression of proinflammatory IL1 or neutrophil chemoattractant CXCL8. Surprisingly, similarly strong local reaction was detected also after application of aluminium hydroxide-based adjuvant. The best balanced local reaction with sufficient activation of immune cells was detected after application of oil-based adjuvants Montanide and Emulsigen.
Keywords: cytokiny; Dendritic Cells; Swine; Th2 buňky; Injections, Intradermal; prasata; adjuvancia imunologická; dendritické buňky; Adjuvants, Immunologic; zvířata; Immunization; Th2 Cells; Cytokines; imunizace; Th1 buňky; injekce intradermální; Th1 Cells; Animals